2020
DOI: 10.1167/tvst.9.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Quantifiable In Vivo Imaging Biomarkers of Retinal Regeneration by Photoreceptor Cell Transplantation

Abstract: Short-term improvements in retinal anatomy are known to occur in preclinical models of photoreceptor transplantation. However, correlative changes over the long term are poorly understood. We aimed to develop a quantifiable imaging biomarker grading scheme, using noninvasive multimodal confocal scanning laser ophthalmoscopy (cSLO) imaging, to enable serial evaluation of photoreceptor transplantation over the long term. Methods: Photoreceptor cell suspensions or sheets from rhodopsin-green fluorescent protein m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Spectral Domain Optical coherence tomography (SD-OCT) is an imaging technique that can provide in vivo morphological evaluation of the transplants after surgery (Li et al, 2017;Liu et al, 2020). Thus, using OCT we assessed the outcome of the hiPSC-RPE graft transplantation 1 week post-surgery and found that all the transplants were located stably at the target position, with no retinal detachment, hemorrhage or any other visible damage to the host tissues (Figures 4G,H).…”
Section: Post-transplantation Surgery Evaluationsmentioning
confidence: 99%
“…Spectral Domain Optical coherence tomography (SD-OCT) is an imaging technique that can provide in vivo morphological evaluation of the transplants after surgery (Li et al, 2017;Liu et al, 2020). Thus, using OCT we assessed the outcome of the hiPSC-RPE graft transplantation 1 week post-surgery and found that all the transplants were located stably at the target position, with no retinal detachment, hemorrhage or any other visible damage to the host tissues (Figures 4G,H).…”
Section: Post-transplantation Surgery Evaluationsmentioning
confidence: 99%
“…95 Similarly, Liu and colleagues applied confocal scanning laser ophthalmoscopy to evaluate in vivo biomarkers of transplanted PR cells qualitatively and quantitatively. They were able to observe migration of the transplanted tissue as well 38. While these 2 techniques demonstrated high resolution and dynamic imaging, it relied on genetically engineered reporter cell lines ( CRX +/tdTomato and Rho +/GFP ) to emit fluorescent light, which is not applicable for future clinical use in human subjects.…”
Section: Post-transplantation Analysismentioning
confidence: 99%
“…They were able to observe migration of the transplanted tissue as well. 38 While these 2 techniques demonstrated high resolution and dynamic imaging, it relied on genetically engineered reporter cell lines (CRX +/tdTomato and Rho +/GFP ) to emit fluorescent light, which is not applicable for future clinical use in human subjects.…”
Section: In Vivo Imaging Tools To Determine Transplant Survival and D...mentioning
confidence: 99%
“… 20 , 21 , 217 Several recent studies have demonstrated the utility of noninvasive imaging for comprehensively studying integration and therapeutic efficacy in hPSC-PRP cell therapies. 160 , 218 The Singh laboratory at Johns Hopkins identified quantifiable biomarkers for tracking fluorescent mouse cells after transplantation, developing a scoring system for multimodal confocal scanning laser ophthalmoscopy (cSLO) imaging. 218 Several properties, including fluorescence size and intensity, graft placement, lamination, and peri-retinal proliferation, were scored longitudinally, facilitating long-term tracking of individual grafts over time.…”
Section: Current Status and Remaining Questions For Retinal Cell Therapiesmentioning
confidence: 99%
“… 160 , 218 The Singh laboratory at Johns Hopkins identified quantifiable biomarkers for tracking fluorescent mouse cells after transplantation, developing a scoring system for multimodal confocal scanning laser ophthalmoscopy (cSLO) imaging. 218 Several properties, including fluorescence size and intensity, graft placement, lamination, and peri-retinal proliferation, were scored longitudinally, facilitating long-term tracking of individual grafts over time. Similarly, Aboualizadeh et al recently used fluorescence adaptive optics scanning light ophthalmoscopy (FAOSLO) to follow individual PRs in vivo in a laser-damage NHP model of PR loss.…”
Section: Current Status and Remaining Questions For Retinal Cell Therapiesmentioning
confidence: 99%